THE EFFECT OF USING EXTENSIVE READING APPROACH TOWARDS STUDENTS’ READING ABILITY - Emil Emil; Melyann Melani; Widya Syafitri (Journal of English Language and Education, 2021)
This research is an quantitative research. The population of this research was the second grade of SMAN 3 Bukittinggi. in this research, the researcher used the purposive sampling technique in determining the sample. There were two classes as the sample of this research. In the experimental class the students were taught by using Extensive Reading Approach. While, in control class the students were taught by using traditional technique and both of classes were given post test at the end of meeting. In order to analyze the data, the researcher used the normality test by using Liliefors test and tested the homogeneity of the data by using F test. The researcher also used the t-test formula to test the hypothesis and consulted its result with the ttable with α = 0.05.